THE STUDY ON THE DISTRIBUTION OF VOLUME IN TRADITIONAL VILLAGE BUILDINGS BY THE MIDDLE REACHES OF NANXIJIANG RIVER IN SOUTHEAST CHINA RURAL AREA - S. T. Li; C. Fan; W. Jie (Lowland Technology International, 2007)
This article is a summary for our studies on the village’s volume in Nanxijiang River drainage area that is in the rural area of Wenzhou in Southeast China Zhejiang province. In this area, many old villages are in their saturation. During our studies, we have found that the volumes including density and plot ratio are distributed in a special way. After statistics, we find out a volume model to describe the villages’ volume distributions and we will use the model tosupport the further constructions in the area.